The microtubule polymerase Stu2 promotes oligomerization of the γ-TuSC for cytoplasmic microtubule nucleation - Gunzelmann, Judith; Rüthnick, Diana; Lin, Dennis Tien-chen; Zhang, Wanlu; Neuner, Annett; Jäkle, Ursula; Schiebel, Elmar (eLife, 2018)
Stu2/XMAP215/ZYG-9/Dis1/Alp14/Msps/ch-TOG family members in association with with γ-tubulin complexes nucleate microtubules, but we know little about the interplay of these nucleation factors. Here, we show that the budding yeast Stu2 in complex with the γ-tubulin receptor Spc72 nucleates microtubules in vitro without the small γ-tubulin complex (γ-TuSC). Upon γ-TuSC addition, Stu2 facilitates Spc72-γ-TuSC interaction by binding to Spc72 and γ-TuSC. Stu2 together with Spc72-γ-TuSC increases microtubule nucleation in a process that is dependent on the TOG domains of Stu2. Importantly, these activities are also important for microtubule nucleation in vivo. Stu2 stabilizes Spc72-γ-TuSC at the minus end of cytoplasmic microtubules (cMTs) and an in vivo assay indicates that cMT nucleation requires the TOG domains of Stu2. Upon γ-tubulin depletion, we observed efficient cMT nucleation away from the spindle pole body (SPB), which was dependent on Stu2. Thus, γ-TuSC restricts cMT assembly to the SPB whereas Stu2 nucleates cMTs together with γ-TuSC and stabilizes γ-TuSC at the cMT minus end.
Gesehen am 16.05.2019